2007
DOI: 10.1001/archopht.125.5.611
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Contact Lens–Related Fusarium Keratitis

Abstract: Objective: To evaluate the specific contact lensrelated or other factors that may contribute to the outbreak of Fusarium keratitis. Methods: A case-control study was conducted of Fusarium keratitis in contact lens users in Singapore from March 1, 2005, to May 31, 2006, and included 61 patients with Fusarium keratitis and 188 populationbased and 179 hospital-based control subjects. Interviewers asked about contact lens solution use and other risk factors. Results: Patients with Fusarium keratitis were more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 15 publications
(15 reference statements)
0
39
0
1
Order By: Relevance
“…The Fusarium outbreak was initially detected via case series in Singapore 53 and in the United States, 54 and was subsequently described in two case control analyses. 55,56 Independent risk factors are reported in Table 4 and both the studies confirmed the excess risk associated with ReNu MoistureLoc. The solution was recalled worldwide by May 2006.…”
Section: Recent Trendsmentioning
confidence: 64%
“…The Fusarium outbreak was initially detected via case series in Singapore 53 and in the United States, 54 and was subsequently described in two case control analyses. 55,56 Independent risk factors are reported in Table 4 and both the studies confirmed the excess risk associated with ReNu MoistureLoc. The solution was recalled worldwide by May 2006.…”
Section: Recent Trendsmentioning
confidence: 64%
“…This is consistent with findings in a Singaporean fungal keratitis case-control study that found that Chinese wearers were at a lower risk of developing Fusarium keratitis. 20 A multicentre cross-sectional survey of contact lens complications in Singapore found that 77% of patients who presented with complications were Chinese. 21 However, no disease-free lens wearing controls were included in the published study.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent outbreaks of fusarial keratitis were recently described in the United States (164 cases) and Singapore (66 cases). Case-control studies in the two populations of patients showed that keratitis was more likely to occur in patients who used a specific contact lens solution (ReNu with MoistureLock) (17,98).…”
Section: Epidemiology and Clinical Spectrum Of Fusariosismentioning
confidence: 99%